2004
DOI: 10.1007/s10658-004-0812-5
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic medium for the semi-selective isolation and enumeration of Xanthomonas axonopodispv. vignicola

Abstract: A semi-selective medium for isolation of Xanthomonas axonopodis pv. vignicola from cowpea (Vigna unguiculata) plant and soil samples was developed. Twelve carbon and five nitrogen sources were tested with four strains of X. axonopodis pv. vignicola, and 25 antibiotics were screened against saprophytes. D D -cellobiose (10 g) was selected as the optimal carbon source. Among the antibiotics, cefazoline inhibited growth of most of the saprophytes with little effect on strains of the pathogen. D D ,L L -methionine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
3
1
2
Order By: Relevance
“…The other dyes had no beneficial effect. In contrast to the findings of Wydra et al (2004), preliminary studies (data not shown) did not find boric acid to have any selective value against the contaminants tested here, even at concentrations as high as 0·03% (w/v). Cefazolin was found to be inferior to cephalexin, especially in suppressing a wider range of Gram-positive contaminants.…”
Section: Discussioncontrasting
confidence: 99%
“…The other dyes had no beneficial effect. In contrast to the findings of Wydra et al (2004), preliminary studies (data not shown) did not find boric acid to have any selective value against the contaminants tested here, even at concentrations as high as 0·03% (w/v). Cefazolin was found to be inferior to cephalexin, especially in suppressing a wider range of Gram-positive contaminants.…”
Section: Discussioncontrasting
confidence: 99%
“…As placas foram incubadas a 28ºC por 48-72 h, quando foi feita a contagem de colônias. A eficácia do meio de cultura foi determinada pela fórmula E (%)=(UFC em meio NYDA com diferentes combinações de antibióticos e fungicidas/UFC em NYDA) × 100 (WYDRA et al, 2004).…”
Section: Methodsunclassified
“…It has been reported that the colonies of Xanthomonas spp. appeared to be yellowish on some media like YPGA, NGA, XTS and MSP due to xanthomonadin production (Mohan & Schaad, 1987;Roumagnac et al, 2000;Schaad & Forster, 1985;Wydra et al, 2004) compared to whitish or creamish colonies on other media like CCM, MXP, BSCAA (Claflin, Vidaver, & Sasser, 1987;Randhawa & Schaad, 1984;Wydra et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To carry out epidemiological and ecological studies, a simple selective medium is required for isolation of Xcm from the infected plants and soil. Semi-selective media have been developed for isolation of several Xanthomonas species and have proved useful for elucidating the ecology and epidemiology of related diseases (Davis, Rott, Baudin, & Dean, 1994;Di, Ye, Schaad, & Roth, 1991;Fessehaie, Wydra, & Rudolph, 1999;Mabagala & Saettler, 1992;Norman & Alvarez, 1994;Sijam, Chang, & Gitaitis, 1992;Wydra, Khatri-Chetri, Mavridis, Sikirou, & Rudolph, 2004). No specific medium for the isolation of Xcm has been reported.…”
Section: Introductionmentioning
confidence: 99%